Proposal for adequacying computer technical courses according pbl methodology - Fernandes, Evelyn; Andrade, Cecília Pereira de; Fantinatti, Pedro Augusto Pinheiro (Revista Hipótese, 2019)
The traditional education is excluding and classificatory. It is archaic and non-democratic. This paper aim to show a proposal of a PBL application in computer technical courses at campus Campinas of IFSP. It has been done a diagnostic of these technical courses and a general proposal has been presented. This work is beeing completed by detailing its proposal.
Keywords: PBL; Project Based Learning; Inclusive Education; Technical Courses; IFSP